Older people in law and society - Herring, Jonathan (Oxford : Oxford University Press, 2009)
Many believe we are facing a demographic time bomb, with an aging population and a decreasing working population. This text analyses the conflicting ways in which the population and the law view this problem and presents possible solutions highlighting the need to protect whilst empowering older people.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Older people -- Legal status, laws, etc. -- Great Britain